THE ROLE AND IMPORTANCE OF BIOMEDICAL ENGINEERING IN UZBEKISTAN, AND THE PRINCIPLES OF ITS DEVELOPMENT - qizi, Olishova Risolat Abduvali (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study examines the role, significance, and principles of biomedical engineering (BME) development in Uzbekistan, emphasizing its impact on healthcare modernization and technological innovation. Method: The research employs a multidisciplinary analysis, integrating insights from medical and engineering sciences, to assess the contribution of BME to healthcare technologies and specialist training. Results: The findings reveal that BME is pivotal in equipping Uzbekistan's healthcare sector with advanced technologies, fostering new treatment methods, and supporting local production of competitive medical devices. Furthermore, the integration of multidisciplinary approaches and innovative technologies has enhanced the sector’s capacity to address complex healthcare challenges and expand its international presence. Novelty: This study underscores the strategic importance of BME in bridging medical and engineering disciplines to promote healthcare and economic development in Uzbekistan. It highlights the untapped potential of BME to revolutionize the country's healthcare system and create opportunities for global competitiveness, contributing to a sustainable healthcare infrastructure and economic growth.